2021
DOI: 10.3390/plants10051027
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Elevated CO2 and Heat on Wheat Grain Quality

Abstract: Wheat is one of the most important staple foods in temperate regions and is in increasing demand in urbanizing and industrializing countries such as China. Enhancing yield potential to meet the population explosion around the world and maintaining grain quality in wheat plants under climate change are crucial for food security and human nutrition. Global warming resulting from greenhouse effect has led to more frequent occurrence of extreme climatic events. Elevated atmospheric CO2 concentration (eCO2) along w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 112 publications
3
38
0
Order By: Relevance
“…About 134%, 126% and 135% higher total NPK uptake was observed under EC 700 over ambient conditions. Increased root biomass and nutrient demand by accumulated biomass are critical factors for increased nutrient uptake under elevated CO 2 conditions [73]. Higher root biomass due to higher allocation of photosynthates and carbon to the roots under higher atmospheric CO 2 was earlier reported by Pendall et al [74].…”
Section: Discussionmentioning
confidence: 72%
“…About 134%, 126% and 135% higher total NPK uptake was observed under EC 700 over ambient conditions. Increased root biomass and nutrient demand by accumulated biomass are critical factors for increased nutrient uptake under elevated CO 2 conditions [73]. Higher root biomass due to higher allocation of photosynthates and carbon to the roots under higher atmospheric CO 2 was earlier reported by Pendall et al [74].…”
Section: Discussionmentioning
confidence: 72%
“…Besides, through the analysis and summary of recent relevant literature, we found that scholars mainly focus on the hot issues including the utilization efficiency of chemical fertilizer (active nitrogen, etc. ), urbanization expansion, greenhouse effects, and pay more attention to the combination of economic, social and ecological benefits of agricultural production to reduce the threat of land use change to food security [ 118 , 119 , 120 , 121 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the minimum temperatures from the heading stage to the physiological maturation stage (13.6 • C) were higher in 2015 than in 2016 (12.6 • C). Higher nocturnal temperatures increased the wheat transpiration rate, which may have decreased the starch accumulation in the grain [49], thus resulting in a lower dilution of grain proteins.…”
Section: Effect Of the Year On Gluten Protein Accumulation During Ripeningmentioning
confidence: 99%